Produção de celulase por fermentação submersa empregando resíduos agroindustriais para a produção de etanol - Rocha, Nattácia Rodrigues de Araújo Felipe (2011)
In this work we studied the production of an enzyme complex generated from agro waste and Aspergillus niger and following the production of bioethanol using the same residue. In preliminary tests we studied the best substrate and was chosen the best strain of micro-organism capable of generating an enzyme complex with good activity in terms of cellulase (FPase). The enzyme complex generated was subjected to a saline precipitation process in order to concentrate the enzyme broth and evaluate the influence of the salting-out process in improving ethanol production. After selecting the substrate and the strain of Aspergillus niger to develop this work we studied the main variables that influence the solid-state fermentation (SSF) and the consequent production of the enzyme complex. At this stage of the work has developed a central composite design (CCP) in order to determine what the best filling volume of the rotating drum reactor used in the production of enzymes. Then varied the temperature and time of FES, the responses were assessed around the proteolytic activities and FPase. Selected conditions of the FES was performed tests simultaneous hydrolysis and fermentation using biomass from the waste from milling rice (RBA) and whey in the production of ethanol. For the fermentation, we used strains of Saccharomyces cerevisiae yeast Y904 as the process of submerged fermentation (SF). Besides adding to the fermentation media, the enzyme complex generated in the FES, the variables such as length of submerged fermentation (SF), temperature and pH were determined according to data from the literature for the production of ethanol from sugar-cane-sugar. Then, we carried out tests with separate hydrolysis to analyze its effect on the optimization of ethanol production. At this stage, varying the hydrolysis time, temperature, pH and volume of enzymes used in hydrolysis and FS separately analyzing in response to ethanol production in g / L. After studying the hydrolysis separately, set the following conditions of employment as the best: 10 hours of hydrolysis, hydrolysis temperature of 35 ° C, pH 4.5 hydrolysis and enzyme volume added to 24 mL of fermentation media, noting that the increase in the volume of enzymes does not provide better results in terms of ethanol production under the conditions tested. It is noteworthy that the increased production of ethanol was obtained using separate hydrolysis. Finally we evaluated the production of the enzyme complex generated by FES in Trichoderma reesei and Aspergillus niger. The tests were performed using the enzyme complexes separately and together and found that strains of A. niger under the conditions tested, were able to produce a more satisfactory evaluating enzyme complex in response to ethanol production.